TEKNIK PELASHINGAN MUATAN KONTAINER ON DECK PADA KAPAL MV.ORIENTAL RUBY UNTUK PENANGGULANGAN PERGESERAN MUATAN - Azis S; Andromeda Vega F (Politeknik Ilmu Pelayaran Semarang, 2019)
ABSTRACT The process of container loading is one of the important things that need to be considered in the implementation of loading and unloading. Good or bad loading of cargo is one of the factors that greatly affect the safety of the cargo, even the stability of the ship when carrying out the voyage. This research aims to further increase knowledge about how to use lashings equipment in accordance with their respective functions as well as better container handling methods. according to the correct procedure. This research was carried out on board the MV. Oriental Ruby, which is one of the fleet owned by PT. SPIL. The twelve-month-one-day research was conducted at the time the authors conducted the Sea Practice (Prala), so that the source of the data was obtained directly from the research site with information-based observations. The results of this study showed that there were still many deficiencies that occurred in the process of carrying out cargo handling, both in terms of knowledge and equipment. The author believes by providing an overview of the method of container sealing, the crew will have knowledge of the technique of cargo loading by increasing the optimization of cargo handling so that there is no shift in load which can have a negative effect on the stability of the ship, or the cargo itself